Benralizumab in Patients With Severe Eosinophilic Asthma With and Without Chronic Rhinosinusitis With Nasal Polyps: An ANANKE Study post-hoc Analysis - D'Amato, Maria; Menzella, Francesco; Altieri, Elena; Bargagli, Elena; Bracciale, Pietro; Brussino, Luisa; Caiaffa, Maria Filomena; Canonica, Giorgio Walter; Caruso, Cristiano; Centanni, Stefano; De Michele, Fausto; Di Marco, Fabiano; et al. (Frontiers in Allergy, 2022)
Background Severe eosinophilic asthma (SEA) in the presence of chronic rhinosinusitis with nasal polyps (CRSwNP) indicates the presence of a more extensive eosinophilic inflammation. Post-hoc analyses from a pivotal clinical trial have demonstrated the enhanced efficacy of benralizumab on asthma outcomes in patients with CRSwNP as a comorbidity. Methods This is a post-hoc analysis from the Italian multi-center observational retrospective ANANKE study. Patients were divided into two groups based on self-reported CRSwNP. Baseline clinical and laboratory features in the 12 months prior to benralizumab prescription were collected. Data of change over time of blood eosinophils, annualized exacerbations rates (AER), asthma control, lung function, oral corticosteroids (OCS) use, and benralizumab discontinuation were collected during the observation period. Results At baseline, the 110 patients with CRSwNP were less frequently female (50.9% vs 74.2%) and obese (9.1% vs. 22.6%) with higher eosinophils (605 vs. 500 cells/mm3) and OCS use when compared to patients without CRSwNP. Similar reductions of AER were seen (-95.8% vs. −91.5% for any exacerbation and −99.1% vs. −92.2% for severe exacerbations in patients with and without CRSwNP, respectively). During benralizumab treatment, comorbid SEA+CRSwNP was associated with a lower risk of any exacerbation (p = 0.0017) and severe exacerbations (p = 0.025). After a mean ± SD exposure of 10.3 ± 5.0 months, half of the SEA+CRSwNP patients eliminated OCS use. No discontinuation for safety reasons was recorded. Conclusions This study helped to confirm the baseline clinical features that distinguish patients with and without CRSwNP being prescribed benralizumab. Numerically enhanced OCS reduction and lower exacerbation risk were observed in patients with SEA and comorbid CRSwNP treated with benralizumab.